Bioimpedance Resistance Indices and Cell Membrane Capacitance Used to Assess Disease Status and Cell Membrane Integrity in Children with Nephrotic Syndrome. (9th May 2019) - Brantlov, Steven; Jødal, Lars; Frydensbjerg Andersen, René; Lange, Aksel; Rittig, Søren; Ward, Leigh C.
Abstract : Background . Accumulation of extracellular water (ECW) is a major clinical manifestation of nephrotic syndrome (NS) in children. Bioimpedance spectroscopy (BIS) is a simple, noninvasive technique that reflects body water volumes. BIS can further measure cell membrane capacitance (C M ), which may be altered in NS. The aims of the study were to explore how BIS measurements could reflect disease status in NS, while avoiding prediction equations which are often only validated in adult populations. Methods . The study involved 8 children (2-10 years) with active NS (ANS group), 5 of which were also studied at NS remission (NSR group), as well as 38 healthy children of similar age (HC group). BIS measurements determined resistances R I N F, R E, and R I (reflecting total body water, extracellular water, and intracellular water) and C M . Also resistance indices based on height (H) were considered, RI = H 2 /R. Results . It was found that R E and R I N F were significantly lower in the ANS group than in both NSR and HC groups (p < 0.001). Corresponding resistance indices were significantly higher in the ANS group than in the NSR (p < 0.01) and the HC (p < 0.05) groups, in accordance with elevated water volumes in NS patients. Indices of intracellular water were not significantly different between groups. C M was significantly lower in the ANS group than in NSR and HC groups (p < 0.05). Conclusion . BIS could distinguish children with active NS from well-treated and healthy children. Studies with more children are warranted.